Structure and composition of Au/Co magneto-plasmonic nanoparticles - Bhattarai, Nabraj; Casillas, Gilberto; Khanal, Subarna; Bahena, Daniel; Velázquez Salazar, J. Jesús; Mejía Rosales, Sergio; Ponce, Arturo; Dravid, Vinayak; Whetten, Robert L.; Mariscal, Marcelo M.; Yacamán, Miguel José (2013)
The fabrication of bimetallic magnetic nanoparticles (NPs) smaller than the size of single magnetic domain is very challenging because of the agglomeration, non-uniform size, and possible complex chemistry at nanoscale. In this paper, we present an alloyed ferromagnetic 4 ± 1 nm thiolated Au/Co magnetic NPs with decahedral and icosahedral shape. The NPs were characterized by Cs-corrected scanning transmission electron microscopy (STEM) and weretheoretically studied by Grand Canonical Monte Carlo simulations. Comparison of Z-contrast imaging and energy dispersive x-ray spectroscopy used jointly with STEM simulated images from theoretical models uniquely showed an inhomo- geneous alloying with minor segregation. The magnetic measurements obtained from superconducting quantum interference device magnet- ometer exhibited ferromagnetic behavior. This magnetic nanoalloy in the range of single domain is fully magnetized and carries significance as a promising candidate for magnetic data recording, permanent magnetization, and biomedical applications.